Sociocultural Dynamics and Their Impact on Speaking Proficiency Among Higher Education Students - Anggriyani, Dian; Pammu, Abidin; Rahman, Fathur; Sahib, Harlinah (Universitas Negeri Semarang, 2025)
This study investigates the sociocultural factors influencing the speaking proficiency of third-semester students at the English Education Department, Mulawarman University. Using a descriptive qualitative approach, twelve participants were purposively selected based on their speaking proficiency levels. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings identify five key sociocultural factors: gender, family background, socio-economic status, exposure to English outside the classroom, social interaction in language learning (interaction with peers, native speakers, and language intsructors). Students with early English exposure, supportive family environments, strong peer networks, and access to technology tend to demonstrate higher fluency and confidence. Despite receiving the same classroom instruction, differences in sociocultural experiences contribute to varied speaking outcomes. This study highlights the need for inclusive teaching strategies that consider students’ backgrounds and individual characteristics. The findings offer insights for educators to design more responsive and equitable language learning environments in EFL contexts.